Clinical outcomes in patients with systemic lupus erythematosus treated with belimumab in clinical practice settings: a retrospective analysis of results from the OBSErve study in Switzerland (Swiss Medical Weekly, 2019)
AIMS OF THE STUDY To describe patterns of systemic lupus erythematosus (SLE) care and the clinical effectiveness of belimumab plus standard of care therapy in a real-world clinical setting in Switzerland. METHODS This multicentre, observational, retrospective cohort study included adults with SLE who initiated belimumab as part of their usual care at least six months before data analysis. The primary outcome was the overall clinical response, assessed by a physician on a Physician’s Global Assessment-like scale, to six months’ treatment with belimumab. Secondary outcomes included improvement in disease activity, SLE manifestations and changes in corticosteroid use. RESULTS 53 patients (81% female) from three hospitals were included. At index (belimumab initiation), 23 patients (43%) had mild, 23 (43%) had moderate, and 7 (13%) had severe SLE. Overall improvement in disease activity in patients receiving belimumab was: ≥80% in 6 patients (11%), ≥50% in 12 (23%), ≥20% in 31 (58%),